Transformative Leadership in Indonesian Islamic Boarding Schools: SDGs-Based Global Insights - Anwar, Sholihul; Sukisno; Raghda Mahmoud (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to map publication trends on transformative leadership in Indonesian Islamic boarding schools (2015–2025) and examine its relevance to curriculum integration, leadership practices, and sustainable education development. Theoretical framework: The study is grounded in Transformative Leadership Theory and aligned with the Sustainable Development Goals (SDGs) framework initiated by the United Nations, particularly SDG 4, SDG 9, SDG 16, and SDG 17, positioning leadership as a driver of sustainable education. Literature review: The literature highlights the role of transformative leadership in improving motivation, organizational culture, and curriculum innovation in Islamic boarding schools, while revealing limited integration with global sustainability and SDGs-oriented perspectives. Methods: A bibliometric analysis of 373 Scopus-indexed articles (2015–2025) was conducted using Biblioshiny to analyze publication trends, thematic structures, and collaboration networks, with SDGs used as an interpretative lens. Results: The findings show a sharp increase in publications since 2018, with Indonesia as the main research hub and dominant themes related to leadership, character education, and human capital development within boarding schools. Implications: The results support SDG 4 by strengthening leadership capacity and inclusive education, SDG 9 through innovation and technology integration, and SDG 16–17 by promoting ethical institutions and research collaboration. Novelty: This study offers a novel SDGs-oriented bibliometric synthesis that integrates global research trends with the local context of Islamic boarding schools, positioning transformative leadership as a bridge between faith-based education and sustainable development.